A dual‐readout nanosensor based on biomass‐based C‐dots and chitosan@AuNPs with hyaluronic acid for determination of hyaluronidase. (20th August 2019) - Liu, Wei; Ding, Fang; Wang, Yanying; Lu, Zhiwei; Zou, Ping; Wang, Xianxiang; Zhao, Qingbiao; Rao, Hanbing
Abstract: A dual‐signal strategy is proposed based on fluorescent biomass‐based carbon dots (BC‐dots) and chitosan stabilized AuNPs (CS@AuNPs) to determine hyaluronidase (HAase). BC‐dots can induce aggregation of CS@AuNPs nanoparticles with a colour change from red to blue. Positively charged CS@AuNPs interacted with the negatively charged hyaluronic acid (HA) through electrostatic adsorption, and CS@AuNPs maintained stability due to the semirigid coil conformation of HA. However, in the presence of HAase, due to enzymatic hydrolysis of HA by HAase, the CS@AuNPs agglomerated. Based on the change of fluorescence and colour, quantitative analysis of HAase was achieved. Linear ranges for the fluorometric and colorimetric determinations were 2.0–70 U mL −1 and 8–60 U mL −1, respectively, with a detection limit of 0.27 U mL −1 . This dual‐signal sensing system possesses high potential for determination of HAase in biological matrices.